Tuning the Properties of Tetracene‐Based Nanoribbons by Fluorination and N‐Doping. Issue 21 (9th September 2019) - Younis, Umer; Muhammad, Imran; Kawazoe, Yoshiyuki; Sun, Qiang
Abstract: The structural stabilities and electronic properties are studied for the recently synthesized one‐dimensional (1‐D) tetracene‐based nanoribbons with four‐membered rings by using first‐principles calculation. All three configurations (named as straight, zigzag, and armchair) are stable and exhibit an indirect band gap of 1.46, 0.73, and 0.32 eV, respectively. The band gaps can be effectively tuned by substituting hydrogen with fluorine atoms and by doping with nitrogen atoms. Substituting hydrogen with fluorine atoms leads to gradual decrease of the electronic band gaps of all configurations. Nitrogen doping changes the band gap from indirect to direct, displaying flexibility of tuning the band structure. Abstract : Tune the gap! The band gaps of tetracene‐based nanoribbons can be effectively tuned by substituting hydrogen with fluorine atoms and by doping with nitrogen atoms. This is shown for different configurations, namely straight, zigzag, and armchair nanoribbons.